Silverlight 4 Business Intelligence Software - Czernicki, Bart (Apress : Imprint: Apress, 2010)
Business intelligence (BI) software allows you to view different components of a business using a single visual platform, which makes comprehending mountains of data easier. BI is everywhere. Applications that include reports, analytics, statistics, and historical and predictive modeling are all examples of business intelligence. Currently, we are in the second generation of business intelligence software-called BI 2.0-which is focused on writing business intelligence software that is predictive, adaptive, simple, and interactive. As computers and software have evolved, more data can be presented to end users with increasingly visually rich techniques. Rich Internet application (RIA) technologies such as Microsoft Silverlight can be used to transform traditional user-interfaces filled with boring data into fully interactive analytical applications that quickly deliver insight from large data sets. Furthermore, RIAs now include 3D spatial-design capabilities that move beyond a simple list or grid and allow for interesting layouts of aggregated data. BI 2.0 implemented via an RIA technology can truly bring out the power of business intelligence and deliver it to an average user on the Web. Silverlight 4 Business Intelligence Software provides developers, designers, and architects with a solid foundation in business intelligence design and architecture concepts for Microsoft Silverlight. This book covers key business intelligence design concepts and how they can be applied without an existing BI infrastructure. Author Bart Czernicki provides you with examples of how to build small BI applications that are interactive, highly visual, statistical, predictive-and most importantly-intuitive to the end-user. Business intelligence isn't just for the executive branch of a Fortune 500 company-it is for the masses. Let Silverlight 4 Business Intelligence Software show you how to unlock the rich intelligence you already have.